ANALISIS KARAKTER TOKOH HAZEL GRACE DAN AUGUSTUS WATERS DALAM NOVEL THE FAULT IN OUR STARS KARYA JOHN GREEN - MANDEROS, FERONIKA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
ABSTRACT Â The research is entitled â€œAnalisis Karakter Tokoh Hazel Grace dan Augustus Waters dalam Novel The Fault In Our Stars Karya John Greenâ€. There are eleven characters in this novel but this analysis only focuses on the two main characters Hazel Grace and Augustus Waters. This research attempts to describe and analyze what are and who the characters are and the character development of Hazel Grace and Augustus Waters in the novel The Fault in Our Stars written by John Green. The data are taken from the novel The Fault in Our Stars by John Green. The indentified data are analyzed according to the concept of Wellek and Warren in describing character development. In analyzing and describing the data the writer uses intrinsic approach according to Edgar V. Roberts. This research shows that the character development of the main characters in the novel is influenced by situation, people, and feelings. This research shows what are the characters and character development of the main characters Hazel Grace and Augustus Waters in the novel The Fault in Our Stars by John Green. at first, Hazel Grace was a girl that loved to be alone, wasting her time only at home, reading books and watching tv. She then became a girl that want to share with others and have friends. Whereas Augustus at first was a boy that thought and tried to handled everything by himself and ignored a help just because he did not want to be pitied, he finally realize that he needed others in his life and being thankful for what the others did to him. ______________________________ Keyword: Main Character, Hazel Grace and Augustus Waters, The Fault in Our Stars Â Â